Genome characterization of Rift Valley fever virus isolated from cattle, goats and sheep during interepidemic periods in Kenya - Onwong'a, A.A.; Oyola, Samuel O.; Juma, John; Konongoi, S.; Nyamota, Richard; Mwangi, Reuben; Muli, Collins; Dobi, Paul; Bett, Bernard K.; Ongus, J.R. (Springer, 2024)
Rift Valley fever virus (RVFV) is a mosquito-borne RNA virus of the Phlebovirus genus in the phenuviridae family. Its genome is trisegmented with small (S), medium (M) and large (L) fragments. In nature, the virus exists as a single serotype that is responsible for outbreaks of Rift Valley fever (RVF), a zoonotic disease that often occurs in Africa and the Middle East. RVFV genomes are thought to undergo both recombination and reassortment and investigations of these events is important for monitoring the emergence of virulent strains and understanding the evolutionary characteristics of this virus. The aim of this study was to characterize the genomes of RVFV isolates from cattle, sheep, and goats collected during an interepidemic period in Kenya between June 2016 and November 2021. A total of 691 serum samples from cattle (n = 144), goats (n = 185) and sheep (n = 362) were analysed at the Central Veterinary Laboratories. The competitive IgM-capture ELISA, was used to screen the samples; 205 samples (29.67%) tested positive for RVFV. Of the 205 positive samples, 42 (20.5%) were from cattle, 57 (27.8%) from goats, and 106 (51.7%) from sheep. All the IgM-positive samples were further analyzed by qPCR, and 24 (11.71%) tested positive with Ct values ranging from 14.788 to 38.286. Two samples, 201808HABDVS from sheep and 201810CML3DVS from cattle, had Ct values of less than 20.0 and yielded whole genome sequences with 96.8 and 96.4 coverage, respectively. There was no statistically significant evidence of recombination in any of the three segments and also phylogenetic analysis showed no evidence of reassortment in the two isolated RVFV segments when compared with other isolates of different lineages from previous outbreaks whose genomes are deposited in the GenBank. No evidence of reassortment leaves room for other factors to be the most probable contributors of change in virulence, pathogenicity and emergence of highly virulent strains of the RVFV.